Perfil eletroforético das proteínas do plasma seminal e sua relação com a congelabilidade do sêmen bovino - Jobim, Maria Inês Mascarenhas (2001)
The objective of this study was to evaluate the protein profile of bovine seminal plasma using two dimensional polyacrilamide gel electrophoresis (2D PAGE) and to find out if any of these proteins was correlated with semen freezability. Seminal plasma was collected from 16 bulls of high and low semen freezability from an artificial insemination center. Twelve protein spots were identified from the 2 D gel (15%), six of which were present in all samples, but only the spots 3 (15 16 kDa), 5 (16 17 kDa) and 7 (10 12 kDa) did not show any variation between bulls. On the seminal plasma samples collected from bulls with high semen freezability, four protei ns showed superior optical densities (P<0,005), the spots 3 (15 16 kDa, pI 4.7 5.2), 7 (11 12 kDa, pI 4.8 4.9), 11 (13 14 kDa, pI 6.0 6,5) and 23 (20 22 kDa, pI 4.8 5.2). On the other hand, the spot 25 (25 26 kDa, pI 6.0 6.5) showed superior optical densit ies (P<0.005) on seminal plasma samples from bulls with low semen freezability . The N terminal amino acid sequence of the spot 7 was identical to the amino terminus of acidic seminal fluid protein (aSFP). The results of the protein 23 sequence after tryps in digestion showed identity to bovine clusterin. Only the spots present on all the samples were analyzed in the 2 D gel (8%). Three protein spots were detected with molecular range and pI from 190 195 kDa, pI 6.5 7.5; 66 kDa, pI 5.4 and 55 kDa, pI 4.5. We stern blot analyses confirmed that the 66 and 55 kDa spots were albumin and osteopontin, respectively. Those two proteins showed superior optical densities (P  0.005) on seminal plasma samples from bulls with high semen freezability. The spot of 190 195 kDa did not show any variation between seminal plasma samples from low and high freezability bulls. The data found in this study suggest that the protein profile differs between low and high bull semen freezability and that clusterin, albumin, osteopotin, and proteins 3 and 7 can be used as a semen freezability markers and protein 25 would be related with low semen freezability.